1987
DOI: 10.1039/dt9870002059
|View full text |Cite
|
Sign up to set email alerts
|

Bis(organoimido)-complexes of tungsten(IV): the crystal and molecular structures of tetrachlorobis(t-butylamine)bis(t-butylimido)bis(µ-p-tolylimido)-ditungsten(VI) and tetrachlorobis(µ-phenylimido)-bis(t-butylamine) bis(t-butylimido)ditungsten(VI)

Abstract: 274ChemInform Abstract The reaction of the phenylimido-bridged W(VI) complex (I) with an excess of the silylamine (II) or with the amine (III) yields the first title complex (IVa). The analogue (IVb)-(IVe), (V) and isomeric mixtures of (VI) are obtained from corresponding dimeric imidotetrachloro-W compounds and silylamines. Molecular and crystal structures of the title complexes (IVa) (space group P21/n, Z=2) and (IVb) (P1, Z=1) are determined. The tert.butylamine ligands are involved in intramolecular NH...C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…1.749(2) W( 5)-N( 13) 2.219(2) W( 5)-Cl (10) 2.5897(6) W( 5)-Cl( 10)#1 2.7986(6) Cl( 10)-W( 5)#1 2.7986(6) N( 13)-C( 61)…”
Section: S14unclassified
See 2 more Smart Citations
“…1.749(2) W( 5)-N( 13) 2.219(2) W( 5)-Cl (10) 2.5897(6) W( 5)-Cl( 10)#1 2.7986(6) Cl( 10)-W( 5)#1 2.7986(6) N( 13)-C( 61)…”
Section: S14unclassified
“…8 This compound has also been prepared in 30% yield in a reaction between WO 2 Cl 2 (DME) and t-BuNH(TMS) in heptane or dimethoxyethane. 9 On the basis of IR studies and by analogy with {W(N-t-Bu)(-NPh)(t-BuNH 2 )Cl 2 } 2 and {W(N-t-Bu)(-Ntolyl)(t-BuNH 2 )Cl 2 } 2 , 10 W(N-t-Bu) 2 Cl 2 (t-BuNH 2 ) was proposed to be a dimer that contains bridging t-butylimido groups. We have confirmed that W(N-t-Bu) 2 (t-BuNH 2 )Cl 2 can be prepared conveniently on a 15 g scale as described by Nielson, but have found through an X-ray structural study that it contains bridging chlorides, not bridging imido groups, as has been assumed in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This compound proved a very attractive starting point for many studies by others in the field, as evidenced by over 100 citations of its report to date (February 2019). Don went on to further elaborate the diversity of metal imido chemistry with co-workers, including John Errington, Alastair Nielson and John Runnacles, including formation of dimeric compounds with bridging arylimido groups as in the α-H exchange reaction shown in scheme 3, equation (2) (15).…”
Section: Appointment To Chair Of Inorganic Chemistry Queen Mary College London 1965mentioning
confidence: 99%
“…However, Don wanted to probe the electronic properties further and the degree of nuclear shielding around the imido nitrogen in the different coordination modes could be revealed by 14 N and 15 N NMR. In an excellent study in collaboration with Ray Richards and Joan Mason from the Nitrogen Fixation unit at the University of Sussex, 14 N and 15 N NMR data for 37 metal imido compounds were recorded and elegantly used to elucidate periodic trends in nitrogen shielding against type of metal, the oxidation state and the charge of the complex, and nature and relative geometry of ancillary ligands. They found that there was surprisingly little de-shielding at nitrogen as the imido M-N-R unit went from linear to bent modes owing to the relatively high energy of the lowest unoccupied molecular orbitals π*(MN) and σ*(MN).…”
Section: Appointment To Chair Of Inorganic Chemistry Queen Mary College London 1965mentioning
confidence: 99%